2022
DOI: 10.3389/fnut.2022.1014502
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism and gut flora profile in different soybean protein induced enteritis of pearl gentian groupers

Abstract: The substitution of high-level soy meals for fish meal (FM) generally leads to fish enteritis, accompanied by significant variations in gut flora. Relevant studies have pointed out a close relationship between tryptophan metabolism mediated by gut flora and vertebrate inflammatory bowel disease. Present study examines the role of tryptophan metabolism and gut flora profile in fish enteritis caused by different soybean meals. The 960 groupers were randomly assigned into 4 groups (n = 4), which including: (1) FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The researchers fed soybean meal to Salmo salar was found to trigger non-infectious subacute enteritis called soybean meal-induced enteritis (SBMIE) (Baeverfjord and Krogdahl 1996). Our past study also found that juvenile pearl gentian grouper were affected by soybean meal in the diet, triggering similar characteristics to above enteritis (Zhang et al 2022a). Currently, the pathogenesis of this enteritis is not clear and there is a lack of treatment.…”
Section: Introductionmentioning
confidence: 83%
“…The researchers fed soybean meal to Salmo salar was found to trigger non-infectious subacute enteritis called soybean meal-induced enteritis (SBMIE) (Baeverfjord and Krogdahl 1996). Our past study also found that juvenile pearl gentian grouper were affected by soybean meal in the diet, triggering similar characteristics to above enteritis (Zhang et al 2022a). Currently, the pathogenesis of this enteritis is not clear and there is a lack of treatment.…”
Section: Introductionmentioning
confidence: 83%
“…Chen et al [25] showed that the reduced growth rate and increased intestinal permeability of Chinese seabass (Lateolabrax maculatus) were related to the changes in intestinal bacterial microbiota and metabolites. A previous study proposed that changes in gut microbiota of fish could alter the metabolism of tryptophan, which in turn affects intestinal physiological functions [26]. In marine medaka (Oryzias melastigma), He et al [27] found that some genera (such as Shewanella and Haloferula) have the capabilities of converting energy, bioremediating, and detoxifying, which has important effects on the metabolic health of marine medaka.…”
Section: Introductionmentioning
confidence: 99%